Study on the Mechanism, Prediction, and Control of Coal Wall Spalling in Deep Longwall Panels Utilizing Advanced Numerical Simulation Methodology. (9th July 2022) - Murmu, Sunny; Budi, Gnananandh
Abstract : This research looked at the occurrence of coal wall spalling, a type of longwall face failure, during the main weighing period (MWP) for panels greater than 300 m depth. FLAC 3D software was exploited to simulate the ground condition of longwall panel 1 of Adriyala Longwall Project mine. The extent and severity of coal wall spalling were quantified using evaluation criteria based on the concepts of vertical stress distribution and maximum shear strain. Subsequently, a parametric analysis of thirteen factors influencing the coal wall spalling was carried out. Empirical equations for predicting coal wall spalling were suggested. Based on the parametric analysis, a coal wall spalling classification system (CWSC) chart is presented to predict spalling characteristics of coal wall that may occur at the MWP. The empirical models depicted good predictive ability with R 2 values greater than 0.9. Parametric analysis revealed that coal wall spalling is highly sensitive to seam compressive strength, mining-induced stress, extraction height, and immediate roof characteristics. The CWSC system's applicability to the five panels was in good agreement with field observations.